Contactin-1 Is Required for Peripheral Innervation and Immune Homeostasis Within the Intestinal Mucosa - Veny, Marisol; Grases, Daniela; Kucharova, Karolina; Lin, Wai Wai; Nguyen, Jennifer; Huang, Sarah; Ware, Carl F.; Ranscht, Barbara; Šedý, John R. (Frontiers in Immunology, 2020)
Neuronal regulation of diverse physiological functions requires complex molecular interactions in innervated tissues to maintain proper organ function. Here we show that loss of the neuronal cell surface adhesion/recognition molecule Contactin-1 (Cntn1) directly impairs intestinal function causing wasting that subsequently results in global immune defects. Loss of Cntn1 results in hematologic alterations and changes in blood metabolites associated with malnourishment. We found thymus and spleen of Cntn1-deficient animals atrophied with severe reductions in lymphocyte populations. Elevated thymic Gilz expression indicated ongoing glucocorticoid signaling in Cntn1-deficient animals, consistent with the malnourishment phenotype. Intestinal Contactin-1 was localized to neurons in the villi and the submucosal/myenteric plexus that innervates smooth muscle. Loss of Cntn1 was associated with reduced intestinal Bdnf and Adrb2, indicating reduced neuromuscular crosstalk. Additionally, loss of Cntn1 resulted in reduced recruitment of CD3+ T cells to villi within the small intestine. Together, these data illustrate the critical role of Contactin-1 function within the gut, and how this is required for normal systemic immune functions.